Athletes' right to Social Security: a comparative analysis of legal guarantees and implementation in ASEAN member states - Oman Sukmana; Tongat Tongat; Lesti Heriyanti; Emy Sri Purwani; Eny Nurwahyuni; Sidik Sunaryo; Muhammad Dhobit Azhary Lubis (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The legal and social position of athletes in ASEAN countries is evolving, yet their access to consistent social security remains limited and fragmented due to unclear employment classification.